From The Podium To Social Media: The Evolution Of Islamic Da'wah In The Digital Era - Yumaira Yus; Andino Maseleno (Greenation Research & Yayasan Global Resarch National, 2025)
The rapid advancement of communication technology has significantly transformed the practice of Islamic da’wah, shifting its delivery from traditional podium-based methods to digital and social media platforms. This paper examines the evolution of Islamic da’wah in the digital era, highlighting the opportunities, challenges, and strategic adaptations required to maintain its effectiveness and ethical foundations. Using a descriptive qualitative methodology with a library research approach, this study analyzes books, scholarly articles, and contemporary research related to digital da’wah. The findings indicate that social media platforms such as YouTube, Instagram, Facebook, and TikTok have expanded the reach of da’wah beyond spatial and temporal limitations, enabling interactive, multimedia, and audience-centered communication. Digital da’wah offers positive impacts, including broader accessibility, two-way interaction, and diverse content formats that appeal particularly to younger generations. However, it also presents challenges such as misinformation, commercialization, algorithm-driven content simplification, and declining digital ethics. Therefore, effective digital da’wah requires strong digital literacy, credible and verified content, ethical communication, sincere intentions, and collaboration among scholars, institutions, and policymakers. The study concludes that while social media is a powerful tool for contemporary da’wah, its success depends on balancing technological innovation with Islamic values and moral responsibility.